Studies on Age-Related Changes in Equine Cheek Teeth Angulation and Dental Drift - Liuti, Tiziana; Daniel, Carola R.; Dixon, Padraic Martin; Reardon, Richard J. M. (Frontiers in Veterinary Science, 2022)
Background Cheek teeth (second through fourth premolars and first through third molars) diastema is a common and painful equine disorder caused by the absence of effective tight interdental contact between these teeth. Limited objective information is available on the angulation of equine cheek teeth that control dental drift or on mesial or distal equine cheek teeth drift that should normally prevent this disorder. Objectives To measure the angulation of the mesial and distal cheek teeth in horses of different ages, quantify age-related cheek teeth mesial and distal dental drift, and measure the cheek teeth row length in horses of different ages. Study Design Retrospective review of computed tomographic images of equine heads. Methods Case details and CT images from clinical equine cases that had undergone standing CT head examination were collated. Three sets of measurements were acquired from each head. “Head size” calculated as the distance between the caudal aspect of the orbit and the caudal aspect of the naso-incisive notch was used to standardize measurements in different sized heads. The length of the cheek teeth rows measured from the mesial aspect of the Triadan 06 occlusal surface to the distal aspect of the Triadan 11 occlusal surface. The rostro-caudal (antero-posterior) position and angulation of the mandibular and maxillary Triadan 06 and 11 teeth were measured in relation to reference lines drawn on CT images. Results Significant mesial drift occurred in the maxillary and mandibular Triadan 11s. Despite their distal angulation, the upper and lower Triadan 06s also drifted mesially. The mean angulation of Triadan 06 and 11 mandibular teeth (17.8 and 26.2°, respectively) was almost double that of maxillary teeth (9.2 and 13.3°, respectively) with both Triadan 11s having greater angulation than the 06s. Cheek teeth angulation only significantly decreased in the mandibular 06s. Cheek teeth arcade lengths decreased with age, but these decreases were not significant. Main Limitations Limitations include the relatively small sample size. Conclusions In the population of horses used for this study, age related mesial drift occurred in both Triadan 06 and 11s, and the angulation of these teeth did not decrease with age in most arcades.